THE RESULTS OF COMPLEX TREATMENT OF HELICOBACTER PYLORI ASSOCIATED FORMS OF STOMACH AND DUODENAL ULCER DISEASE IN THE POPULATION OF MAZARI SHARIF PROVINCE OF THE ISLAMIC REPUBLIC OF AFGHANISTAN - KHAYRIDDIN KHOZHI RAMAZON; YU.A. SHOKIROV; S.S. JALILOV (Avicenna Tajik State Medical University, 2017)
Objective: To study the effectiveness of eradication therapy in patients with H. pylori-associated forms of stomach and duodenal ulcer disease. Methods: In 88 patients with Helicobacter-associated forms of stomach and duodenal ulcer disease on the basis of clinical, endoscopic, bacteriological methods with PCR formulation, the effectiveness of the Maastricht scheme of triple therapy was studied. The patients were divided by age, gender and the nature of ulcerative lesions. The effectiveness of treatment was assessed by the following criteria: abating of clinical symptoms, cicatrization of ulcerative defect and degree of eradication of H. pylori. Results: The obtained data showed that complete scarring of «single» stomach ulcers reached 100.0%, and eradication in 80.0% of patients. With «multiple» ulcers scarring was observed in 60.0%, and eradication - in 80.0% of cases. With «round» and «peptic» stomach ulcers, scarring took place in 16.7%, and eradication occurred in 33.3% of patients, while in the duodenum, these indicators were relatively higher - 40.0% and 60.0% respectively. In the general population of the examined patients with gastric ulcer, scarring reached 60.0%, eradication - up to 71.8%; the best indicators were noted for peptic ulcer disease - 83.9% and 87.5%, respectively. Conclusion: Three-component eradication therapy Helicobacter-associated forms of stomach and duodenal ulcer disease with the prescription of Clarithromycin, Amoxicillin in combination with Omeprazole is quite highly effective. The results of treatment are definitely dependent on the location and nature of the ulcerative lesion, H. pylori strains and the patient's age.